ChemInform Abstract: An Acid/Base‐Regulated Recyclable Strategy for Homogeneous Cinchona Alkaloid‐Derived Primary Amine Organocatalysts in Aldol, Vinylogous Michael and Double‐Michael Cascade Reactions. Issue 4 (January 2016) - Wan, Jingwei; Zhao, Zhiwei; Wang, Falu; Ma, Xuebing
Abstract: Organocatalysts (I) are applied in the title reactions according to conditions A)—C).